Heterojunction Hybrid Devices from Vapor Phase Grown MoS(2) - Yim, Chanyoung (Nature Publishing Group, 2014)
We investigate a vertically-stacked hybrid photodiode consisting of a thin n-type molybdenum disulfide (MoS(2)) layer transferred onto p-type silicon. The fabrication is scalable as the MoS(2) is grown by a controlled and tunable vapor phase sulfurization process. The obtained large-scale p-n heterojunction diodes exhibit notable photoconductivity which can be tuned by modifying the thickness of the MoS(2) layer. The diodes have a broad spectral response due to direct and indirect band transitions of the nanoscale MoS(2). Further, we observe a blue-shift of the spectral response into the visible range. The results are a significant step towards scalable fabrication of vertical devices from two-dimensional materials and constitute a new paradigm for materials engineering.